2004
DOI: 10.1002/bies.20159
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious transposable elements and the extinction of asexuals

Abstract: The genomes of virtually all sexually reproducing species contain transposable elements. Although active elements generally transpose more rapidly than they are inactivated by mutation or excision, their number can be kept in check by purifying selection if its effectiveness becomes disproportionately greater as their copy number increases. In sexually reproducing species, such synergistic selection can result from ectopic crossing-over or from homologous recombination under negative epistasis. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 102 publications
7
107
2
Order By: Relevance
“…Its short 5Ј and 3Ј noncoding regions comprise 133 and 74 bp, respectively. A TATA-like sequence, (TA) 5 , at position 86 is expanded to (TA) [6][7][8] in some copies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its short 5Ј and 3Ј noncoding regions comprise 133 and 74 bp, respectively. A TATA-like sequence, (TA) 5 , at position 86 is expanded to (TA) [6][7][8] in some copies.…”
Section: Resultsmentioning
confidence: 99%
“…An additional possibility dependent on sexual reproduction is recombination with synergistic epistasis, and, at least in some species and perhaps generally, there are silencing mechanisms associated with meiosis. Therefore, we have suggested that the absence of these various mechanisms in asexuals may lead to the unchecked intragenomic proliferation of retrotransposons and may be a major factor responsible for the relatively early extinction of lineages that abandon sexual reproduction and, correspondingly, for the advantage of sex over asex (6,7). In that case, ancient asexuals, if they exist, would be expected to lack intact transposable elements, except for those that are introduced by horizontal transmission or that serve some function advantageous to their host, and are subject to limiting mechanisms not dependent on sex.…”
mentioning
confidence: 99%
“…Some theories predict that transposable elements should be either absent from the genomes of asexuals 18 or undergo unrestrained expansion after the switch to asexuality, potentially leading to species extinction unless transposable element proliferation is prevented 19 . We found that transposable elements cover about 3% of the A. vaga genome, which is less than the percentage reported in most other metazoans (including the genome of the obligate parthenogenetic nematode Meloidogyne incognita, 36% of which is made up of repetitive elements 20 ).…”
Section: Research Lettermentioning
confidence: 99%
“…Although some CAs are selectively advantageous, there are also negative consequences to a mechanism that generates high rates of CAs. Selection against cells with high levels of genome instability, reflecting high levels of transposable elements, may be one mechanism by which the number of such elements per genome is limited (32). In higher eukaryotes such as humans, whose genomes are replete with repetitive DNA, a compromise between opportunities for variation and excessive genome instability could be accomplished by increasing the efficiency of local interactions (end rejoining and sister chromatid recombination) and by shifting the balance of DSB repair from homologous to nonhomologous pathways.…”
Section: Cgh-arraymentioning
confidence: 99%